2023
DOI: 10.1186/s41021-023-00271-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression analysis reveals different heat shock responses in indigenous (Bos indicus) and crossbred (Bos indicus X Bos taurus) cattle

Abstract: Environmental heat stress in dairy cattle leads to poor health, reduced milk production and decreased reproductive efficiency. Multiple genes interact and coordinate the response to overcome the impact of heat stress. The present study identified heat shock regulated genes in the peripheral blood mononuclear cells (PBMC). Genome-wide expression patterns for cellular stress response were compared between two genetically distinct groups of cattle viz., Hariana (B. indicus) and Vrindavani (B. indicus X B. taurus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…It was also observed that the enrichment of genes in the neuroactive ligand-receptor interaction pathway ( CALCR , GRIA4 , GRM8 , GHR, MC5R, NPFFR2, PRLH, UCN3 ), PI3K-Akt signaling pathway ( CDKN1B, GHR, IL6, MTOR, OSM, SGK1 , TLR4 ), HIF-1 signaling pathway ( CDKN1B, IL6, MTOR and TLR4 ) and JAK–STAT signaling pathway ( LIF, GHR, IL6, MTOR and OSM ) with other pathways and stress responses ( Figure 3C ). In line with these pathways ( Figure 3C ), the previous studies found that the candidate genes for HS response enriched HSF1 mediated heat shock response, estrogen signaling pathway, HIF-1 signaling pathway, PI3K-Akt signaling pathway, MAPK singling pathway and immune response pathways in dairy cattle ( 93 , 112 , 113 ).…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...supporting
confidence: 74%
“…It was also observed that the enrichment of genes in the neuroactive ligand-receptor interaction pathway ( CALCR , GRIA4 , GRM8 , GHR, MC5R, NPFFR2, PRLH, UCN3 ), PI3K-Akt signaling pathway ( CDKN1B, GHR, IL6, MTOR, OSM, SGK1 , TLR4 ), HIF-1 signaling pathway ( CDKN1B, IL6, MTOR and TLR4 ) and JAK–STAT signaling pathway ( LIF, GHR, IL6, MTOR and OSM ) with other pathways and stress responses ( Figure 3C ). In line with these pathways ( Figure 3C ), the previous studies found that the candidate genes for HS response enriched HSF1 mediated heat shock response, estrogen signaling pathway, HIF-1 signaling pathway, PI3K-Akt signaling pathway, MAPK singling pathway and immune response pathways in dairy cattle ( 93 , 112 , 113 ).…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...supporting
confidence: 74%